CD8 Positive T Lymphocyte Infiltration of Liver Metastases of Uveal Melanoma: A Case Report - Takahashi, Naoki; Tajiri, Kazuto; Kagoyana, Ko; Tanaka, Shinichi; Yasuda, Ichiro (Frontiers in Oncology, 2021)
A 78-year-old Japanese man was referred for examination of multiple small nodules on his liver detected by magnetic resonance imaging (MRI). These small nodules were hyperintense on T1-weighted MRI, and were in hepatobiliary phase on gadolinium-ethoxybenzyl-diethylenetriamine pentaacetic acid enhanced MRI. Five years earlier, he had undergone curative enucleation of his left eye for uveal melanoma. US-guided biopsy revealed that the liver nodules were metastases of melanoma. Pathological examination also showed infiltration of CD8 positive T lymphocytes. The metastatic nodules remained unchanged for more than 2 years and he was not further treated. This pathology and clinical course suggest that the systemic immune response of the host could suppress hepatic metastases of uveal melanoma.